Screening of type 2 diabetes mellitus patients for their macrovascular complications in tertiary care hospital - B., Ragul; K., Kiran P.; Gupta, A. K. (International Journal of Advances in Medicine, 2019)
Background: Type2 diabetes is characterized by a long asymptomatic period commonly to be diagnosed when complications appear. The risk factors associated with diabetes are age, hypertension, dyslipidemia, smoking, alcohol, obesity & others. The role of early detection and adequate treatment of diabetes and related complications patients and health services is the basis for present study. Methods: The present study was conducted at S.N. Medical College, Agra, India on 86 consecutive newly diagnosed cases of type 2 diabetes. All individuals aged ≥ 20 years of age, who were not known diabetic, presenting to medicine department were included in the study for the targeted and opportunistic screening duration of January 2011 to June 2012. Results: The prevalence rates of vascular complications in this study group were analyzed statistically. The findings are the mean age was 54.27±9.27 years. 72.09% of newly diagnosed type 2 diabetes patients were aged above 50 years. Maximum number of patients were overweight (37.20%) followed by obese (32.55%). Hypertension was present in 30.23%, prevalence of CAD was 9.30%, and none had evidence of PVD and Cerebrovascular disease. Conclusions: Macrovascular complications were present in 9.30% of asymptomatic newly diagnosed type 2 diabetes patients. In the study present study found that there was a significant association of these risk factors were identified and treated as early as possible to decrease the progression of vascular complications.